Shariah-Compliant or Shariah-Based? The Changing Discourse of Islamic Finance - Ali Reza Ramrouz; Mohammad Reza Simiari (تحقیقات مالی اسلامی (پیوسته))
Observers and experts of the Islamic finance industry expect Islamic financial institutions to move from offering instruments that are solely Shariah-compliant to offering instruments that are substantially Shariah-based. However, there are some questions about when the words "Shariah-compliant" and "Sharia-based" entered into the Islamic financial literature and why. What is the exact meaning of "Shariah-based"? In this article, in addition to reviewing different attitudes towards the Islamic financial system, we will describe the history of the emergence of the two mentioned terms as a manifestation of the change of discourse in the Islamic financial industry. Investigations show that in the definition of Sharia-based product, at least one of the principles of separation (emphasis on the content separation of Islamic finance from conventional finance), Authenticity and welfare have been implied. The principle of separation refers to the concepts of separate product development, separate pricing, separation of funds and sectoral separation. The principle of authenticity deals with the three concepts of historical authenticity, authentic connection to the real economy and ontological transparency. Concepts in the welfare principle include risk-sharing, protection of the poor, and welfare-oriented business operations. This change in the discourse is not a problem, but a sign of Islamic financial maturity and moving towards the goals of the Islamic economic system.